Community Assistance in Understanding Household Poverty Lines as a Basis for Household Economic Planning in Selected Areas of Medan City - Muammar Rinaldi; Mutiara Shifa; Mela Novita Rizki; Rotua Sahat Pardamean Simanullang; Ellys Siregar (Outline Journal of Community Development, 2026)
Limited public understanding of the household poverty line has hindered effective household economic planning. This community service program aimed to improve community literacy regarding the household poverty line as a foundation for household economic planning. The program was conducted in several areas of Medan City, including Jalan Halat (Pasar Halat and surrounding areas), Jalan Platina IV Gang Ano, Jalan Damar Wulan Sampali, Jalan Nabung Surbakti and Kacaribu, and Jalan Tuamang. The implementation consisted of community needs assessment, educational sessions, interactive discussions, mentoring, practical exercises on calculating household poverty status, and program evaluation. A total of 20 participants actively attended the program. The results demonstrated an improvement in participants' understanding of the household poverty line, their ability to identify their household economic conditions using the applicable indicators, and their awareness of preparing household financial plans through simple income and expenditure records. The classification results showed that 10 participants were categorized as non-poor, 4 as nearly non-poor, 3 as nearly poor, and 3 as poor. Overall, the program contributed positively to improving community economic literacy and increasing participants' awareness of managing household finances more systematically to strengthen household economic resilience.